Proposed Marketing Strategies and Implementation Plans to Increase XRF Sales in Indonesia’s Nickel Mining Sector - Hanafani, Alvian Iacocca (Eduvest - Journal of Universal Studies, 2025)
The nickel mining sector in Indonesia has shown tremendous growth due to increasing global demand for nickel ore. Over the five years to 2022, production from Indonesia increased by a CAGR of 24% and is expected to rise by a CAGR of 13% between 2023 and 2027. Mining activity is strongly related to the use of analyzing equipment to analyze what kind of element that consists in the nickel ore. The equipment is called XRF or X-Ray Fluorescence. However, this opportunity may also be used by the competitors. There are approximately 4 XRF distributor companies, each company carries different brands of XRF. PT Rindu Makmur is authorized distributor of Vasilon 4 XRF in Indonesia, currently experiencing stagnancy of XRF unit sold, while from 2021 to 2024 there are only 30 units sold meanwhile the nickel mining companies always increasing until 470 companies in 2024. In the midst of increasingly fierce competition with competitors, PT Rindu Makmur must implement new marketing strategies to strengthen its position and increase sales of the XRF Vasilon. In this study the authors analyzed what are the new marketing strategies, the new 7P’s of marketing mix and what are the implementation plans of the new marketing strategies. Those strategies in this study were first analyzed based on internal analysis, external analysis and then determining marketing strategy analysis with SWOT Analysis and TOWS analysis. After that the author also gives the recommendation for further analysis and to PT Rindu Makmur.